Are methodological quality and completeness of reporting associated with citation-based measures of publication impact? A secondary analysis of a systematic review of dementia biomarker studies. Issue 3 (22nd March 2018) - Mackinnon, Shona; Drozdowska, Bogna A; Hamilton, Michael; Noel-Storr, Anna H; McShane, Rupert; Quinn, Terry
Abstract : Objective: To determine whether methodological and reporting quality are associated with surrogate measures of publication impact in the field of dementia biomarker studies. Methods: We assessed dementia biomarker studies included in a previous systematic review in terms of methodological and reporting quality using the Quality Assessment of Diagnostic Accuracy Studies (QUADAS) and Standards for Reporting of Diagnostic Accuracy (STARD), respectively. We extracted additional study and journal-related data from each publication to account for factors shown to be associated with impact in previous research. We explored associations between potential determinants and measures of publication impact in univariable and stepwise multivariable linear regression analyses. Outcome measures: We aimed to collect data on four measures of publication impact: two traditional measures—average number of citations per year and 5-year impact factor of the publishing journal and two alternative measures—the Altmetric Attention Score and counts of electronic downloads. Results: The systematic review included 142 studies. Due to limited data, Altmetric Attention Scores and electronic downloads were excluded from the analysis, leaving traditional metrics as the only analysed outcome measures. We found no relationship between QUADAS and traditional metrics. Citation rates were independently associated with 5-year journal impact factor (β=0.42; p<0.001), journal subject area (β=0.39; p<0.001), number of years since publication (β=-0.29; p<0.001) and STARD (β=0.13; p<0.05). Independent determinants of 5-year journal impact factor were citation rates (β=0.45; p<0.001), statement on conflict of interest (β=0.22; p<0.01) and baseline sample size (β=0.15; p<0.05). Conclusions: Citation rates and 5-year journal impact factor appear to measure different dimensions of impact. Citation rates were weakly associated with completeness of reporting, while neither traditional metric was related to methodological rigour. Our results suggest that high publication usage and journal outlet is not a guarantee of quality and readers should critically appraise all papers regardless of presumed impact.